The concept of 'Russification' as understood by Professor P.V. Znamensky - T.M. Nekhorosheva (Ученые записки Казанского университета: Серия Гуманитарные науки)
Nowadays, many polysemantic terms that are widely used in history, such as Russification, should be studied in detail and have their meanings clarified. This article analyzes the concept of Russification in the works of Pyotr Vasilyevich Znamensky (1836–1917), a historian and professor of the Kazan Theological Academy. The main structural components that are, to some extent, characteristic of Russification are revealed: linguistic community, unity of faith, and political loyalty. P.V. Znamensky’s attitude toward each of these elements in the context of the national policy problem in the Russian Empire is considered. The results obtained show that he did not support the idea that small-numbered peoples should have immediately switched to the Russian language in their liturgical life and education. Instead, he was a consistent supporter of N.I. Ilminsky’s system, entailing that non-Russian-speaking peoples should have been educated in their national languages. For P.V. Znamensky, Russification most often implied the Christianization of these peoples. According to him, Russification meant that the peoples of the Russian Empire loved the state and the emperor and were loyal to the authorities. At the same time, with the Russians over time.